Rancang Bangun Aplikasi Customer Relationship Management (CRM) Berbasis Web pada CV. Adiyasa Teknik - Bagas Afrizal; Farizi Ilham; Nicholas; Rama Achmad Fadillah (CV. Shofanah Media Berkah, 2026)
Adiyasa Teknik is an electronics service and installation business in Tangerang that still manages all its operational processes manually using physical notebooks. This condition causes various problems, including inaccurate customer data, difficulty in retrieving service history, lack of spare parts stock management, unstructured technician coordination, and absence of comprehensive operational reports. To address these issues, a web-based Customer Relationship Management (CRM) application was developed using Node.js, Express.js, Next.js, TypeScript, and MySQL with an Agile development approach. The application covers five main modules: customer data management, service order management (Kanban pipeline), activity management, quotation management, and automated reports with dashboard. System testing was conducted using the Black Box Testing method and demonstrated that all system functions operate according to user requirements. With the implementation of this CRM system, CV. Adiyasa Teknik can manage its operational data digitally, in a structured and integrated manner, thereby improving service efficiency and the quality of management decision-making.